Everolimus, an mTOR pathway inhibitor, is highly successful on ovarian hyperstimulation syndrome by reducing ovarian weight and progesterone levels: a preclinical experimental randomized controlled study. (2nd September 2015) - Kosmas, Ioannis P.; Kitsou, Chrysoula; Lazaros, Leandros; Markoula, Sofia; Peschos, Dimitrios; Mynbaev, Ospan; Tournaye, Herman; Prapas, Nikolaos; Prapas, Ioannis; Zikopoulos, Athanasios; Galani, Vasiliki; Georgiou, Ioannis
Abstract: The usefulness of various pathways inhibitors, Everolimus, an inhibitor of mammalian target of rapamycin (mTOR), Infliximab, a monoclonal antibody which blocks the tumor necrosis factor-a (TNF-a), Erlotinib, a tyrosine protein kinase inhibitor of the epidermal growth factor receptor (EGFR), Metformin, an activator of AMP-activated protein kinase enzyme (AMPK) and vascular permeability reducers were explored in an ovarian hyperstimulation syndrome (OHSS) rat model. Sixty-three female Wistar rats were randomly divided in seven groups. The control group received saline, while the OHSS group received recombinant – follicle-stimulating hormone (rec-FSH) for four consecutive days. The other five groups received rec-FSH for 4 d and Everolimus daily, Infliximab once, Erlotinib daily, Metformin daily and Vitamin C daily, respectively. All groups received human chorionic gonadotropin (hCG) at the fifth day. The efficacy of Everolimus administration for various intervals was also explored. Significantly reduced ovarian weight was observed in the Everolimus group (rec-FSH + hCG + mTOR inhibitor) compared to the OHSS group ( p < 0.001). The Everolimus group also showed the lowest progesterone (PRG) concentration ( p = 0.007). The Erlotinib group (rec-FSH + hCG + EGFR inhibitor) presented with the lowest graafian follicle number, while the Everolimus group was characterized by the lowest corpus luteum number. The vascular permeability and the estradiol levels did not differ between groups. Finally, the Everolimus intra-comparison showed no difference in all measured outcomes. Studying the different pathways linked to vascular endothelial growth factor (VEGF) pathway, we conclude that targeting mTOR pathways is beneficial for reducing ovarian weight and PRG levels in an OHSS animal model. Chinese abstract: 用于抑制各种通路的抑制剂依维莫司，一种哺乳动物雷帕霉素靶蛋白抑制剂(mTOR)，英夫利西，阻碍肿瘤坏死因子-α（TNF-α）的一种单克隆抗体，埃罗替尼，表皮生长因子(EGFR)的酪氨酸蛋白激酶受体抑制剂，二甲双胍，腺苷酸活化蛋白激酶（AMPK）催化剂和血管通透性缩减剂被探索应用于卵巢过度刺激综合征（OHSS）的大鼠模型。 63只雌性wistar大鼠被随机分为7组 。对照组使用生理盐水，OHSS组连续四天给予重组卵泡刺激素（rec-FSH）.其余五组处理方式分别为给予rec-FSH 4天和依维莫司每日一次，英夫利西一次，埃罗替尼每日一次，二甲双胍每日一次和维生素C每日一次。所有组别均在第五天给予人绒毛膜促性腺激素(hCG). 同时探究了在不同间期依维莫司处理的疗效。依维莫司组（rec-FSH + hCG + mTOR 抑制剂）与OHSS组相比观察到了显著的卵巢重量降低（p<0.001）。依维莫司组同时也表现出了最低的孕酮浓度 (p=0.007). 埃罗替尼组（rec-FSH + hCG + EGFR 抑制剂）格拉夫卵泡的数量最少，而依维莫司组以最少的黄体为特征。血管通透性和雌二醇水平各组并无差异。最后，依维莫司的组间比较表明所有数据均无差异。根据对相关血管内皮生长因子通路相关不同通路的研究，我们推断靶向mTOR通路有利于减少OHSS模型动物的卵巢重量和PRG水平。